Upaya Guru Dalam Meningkatkan Pengetahuan Sains Melalui Pendekatan Eksplorasi Lingkungan Sekitar Di TK Kembang Seroja - Astuti Hardiyanti; Ihlas Ihlas; Sri Wahyuningsih; Ade S Anhar (GUIDING WORLD (BIMBINGAN DAN KONSELING), 2024)
This research aims to enhance the understanding of children at TK Kembang Seroja in the field of science through the approach of environmental exploration. The study employed a classroom action research method combining both quantitative and qualitative approaches. The participants involved 34 children from TK Kembang Seroja Group B. Data analysis utilized descriptive percentage and descriptive analysis of children's activities. Data validity was confirmed through content validity. The results indicated that the environmental exploration approach successfully improved the children's scientific understanding. Initially, before the intervention, the average scientific understanding of the children was 31%. However, after implementing the classroom action research with the environmental exploration approach, the average understanding increased to 41%. In the second cycle, the average understanding further rose to 59%, and by the third cycle, the children's average understanding reached the targeted goal of 83%.The selection of suitable teaching methods is crucial in achieving educational objectives. All educational goals should be integrated into the curriculum as guidelines for teachers. However, curriculum implementation relies on the competence of teachers. The ability of teachers to plan, execute, and evaluate teaching significantly determines the selection of appropriate methods. The use of the environmental exploration approach to enhance scientific understanding has proven successful in the Classroom Action Research at TK Kembang Seroja.